KONFLIK DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. IMPERIAL GRAHA PROPERTINDO - Mursidah, Ida (UP2M SEKOLAH TINGGI ILMU EKONOMI GALILEO, 2018)
This research aims to determine the effect of conflict and work environment either partially or simultaneously on employee performance at PT. Imperial Graha Propertindo. The result of the research shows that there is no positive and significant influence between conflict and employee performance with the result of t test. With a value of 0.492 t count is greater than t table 3.81 with a significant value of 0.631, this value is greater than 0.05. There is no positive and significant influence between work environment and employee performance with the result of t test. With t count value 2.356 smaller than t table 3.81 with significant value 0.03, this value is smaller than 0.05. There is a positive and significant influence between conflict and work environment simultaneously on the performance of employees in targeted with test results f. With the f value of 6,602 is bigger than f table 3.18.